Prevalence of Undernutrition and Associated Factors among Pregnant Women in a Public General Hospital, Tigray, Northern Ethiopia: A Cross-Sectional Study Design - Ebud Ayele; Guesh Gebreayezgi; Teklewoini Mariye; Degena Bahrey; Gebrekiros Aregawi; Gebregziabher Kidanemariam (Journal of Nutrition and Metabolism)
Background. Undernutrition is a global health problem, particularly in pregnant women. Despite the limited studies performed in different parts of Ethiopia, the information about the prevalence of undernutrition of pregnant women in the current study area is not documented. Therefore, this study aimed to assess the prevalence of undernutrition and associated factors in pregnant women. Methods. An institution-based cross-sectional study design was conducted in the Tigray region from August 01 to December 30, 2018. Study subjects were selected by systematic sampling technique from the respective hospitals. An interviewer-administered questionnaire was used to collect the data. Data were cleaned and entered using Epi-Data version 3.1 and then exported to statistical package for social science (SPSS) version 23.0 for analysis. Multivariate analyses were carried out, and adjusted odds ratios (AORs) with 95% CI and significance level (p value) <0.05 were considered. Results. Out of the total 844 selected pregnant women, 840 participated in the study, yielding a response rate of 99.5%; of this, respondent’s undernutrition prevalence was found to be 40.6% with 95% confidence interval (38.93% and 42.27%). Agriculture as occupation (AOR = 2.6, 95% CI: 1.5, 4.5), women who wanted the pregnancy (AOR = 0.25, 95% CI: 0.14, 0.448), no history malaria during pregnancy (AOR = 0.291, 95%: (0.152, 0.555)), coffee intake during pregnancy (AOR = 1.6, 95% CI: 1.04, 2.69), and hemoglobin < 11 g/dl (AOR = 4.9, 95% CI: 3.09, 7.8) were the factors that were significantly associated with undernutrition, p value (<0.05). Conclusion. In this study, occupation, history of having malaria during pregnancy, wanted type pregnancy, coffee intake during pregnancy, and hemoglobin < 11 g/dl were factors significantly associated with undernutrition in pregnant mothers. So, healthcare providers, policymakers, and other stakeholders should give special focus on these factors.